Effect of land- and aquatic-based plyometrics on spike and block reaches in young volleyball players: a pilot study - Hubert M.* (2023)
© 2023 Universidade Estadual Paulista - UNESP. All rights reserved.Aim: The purpose of this pilot study was to analyze the feasibility of the intervention and measures of a six-week land- and aquatic-based plyometric training on spike and block reaches in young volleyball athletes. Methods: Twelve female players were divided into a land group (LG) (n = 6, 12.4 ± 0.3 years, 1.61 ± 0.04 m, 57.0 ± 9.3 kg) and a water group (WG) (n = 6, 12.5 ± 0.5 years, 1.57 ± 0.06 m, 48.9 ± 8.5 kg). The spike and block (without step, with slide step, and with crossover step) reach and countermovement jump height were evaluated before and after a 6-week plyometric training protocol. Duration (total and of each session), adhesion and adherence, and safeness of the intervention; completion of assessments, within-trial reliability, and variability of the outcome measures and preliminary results were the variables of interest. To analyze the effect of the training on jump performance, the Wilcoxon test was used (p < 0.05), and effect sizes (r) were calculated. Results: All participants concluded the intervention and the assessments as planned. No dropouts or adverse events were registered during the study. The within-trial reliability for all assessment tests was considered excellent (ICC ≥ 0.9). Preliminary results indicate that LG improved the reach of the spike and block with the slide step; and that WG improved the spike, block with the slide step to the left, and block without movement reaches (p < 0.05; large effect size). Conclusion: An intervention of six weeks of plyometric training on land and in water is feasible, and preliminary results indicate that both training protocols may benefit the performance of spike and block in young volleyball athletes.